HOSPITAL PERCEPTION OF A CRM SYSTEM: A STUDY OF CRITICAL FACTORS IN PRIVATE HOSPITALS IN MALAYSIA (Journal of Information and Communication Technology, 2012)
The aim of this study was to identify the factors that might influence perception about the benefits of a Customer Relationship Management (CRM) system, and the direction of this influence in private hospitals in Malaysia. Three factors (innovation, organizational, and environmental factors) were identified as influencing perception about the benefits of a CRM system. The study deployed a quantitative research approach, using a questionnaire to collect data. Private hospitals in the northern part of Malaysia were selected using the area sampling method and convenience sampling, and the management of the hospitals became the target respondents. For the survey, the research questionnaire was distributed to the sample of the study and each respondent was given a month to complete the questionnaire. The collected data was analyzed using Backward Multiple Regression Analysis. The results revealed that innovation and environmental factors had a positive significant relationship on perception, while the organizational factor had a significant negative relationship. The results are expected to help the decision makers of hospitals to better plan for the adoption and implementation of CRM systems. In addition, it will benefit the vendors of CRM systems toward a better understanding of the needs of hospitals to be able to expand their market in the healthcare industry.